Acinetobacter variabilis sp. nov. (formerly DNA group 15 sensu Tjernberg & Ursing), isolated from humans and animals - Krizova, Lenka; McGinnis, Jana; Maixnerova, Martina; Nemec, Matej; Poirel, Laurent; Mingle, Lisa; Sedo, Ondrej; Wolfgang, William; Nemec, Alexandr (International journal of systematic and evolutionary microbiology, 2015)
We aimed to define the taxonomic status of 16 strains which were phenetically congruent with Acinetobacter DNA group 15 described by Tjernberg & Ursing in 1989. The strains were isolated from a variety of human and animal specimens in geographically distant places over the last three decades. Taxonomic analysis was based on an Acinetobacter-targeted, genus-wide approach that included the comparative sequence analysis of housekeeping, protein-coding genes, whole-cell profiling based on matrix-assisted laser desorption ionization-time-of-flight mass spectrometry (MALDI-TOF MS), an array of in-house physiological and metabolic tests, and whole-genome comparative analysis. Based on analyses of the rpoB and gyrB genes, the 16 strains formed respective, strongly supported clusters clearly separated from the other species of the genus Acinetobacter. The distinctness of the group at the species level was indicated by average nucleotide identity values of ≤82 % between the whole genome sequences of two of the 16 strains (NIPH 2171(T) and NIPH 899) and those of the known species. In addition, the coherence of the group was also supported by MALDI-TOF MS. All 16 strains were non-haemolytic and non-gelatinase-producing, grown at 41 °C and utilized a rather limited number of carbon sources. Virtually every strain displayed a unique combination of metabolic and physiological features. We conclude that the 16 strains represent a distinct species of the genus Acinetobacter, for which the name Acinetobacter variabilis sp. nov. is proposed to reflect its marked phenotypic heterogeneity. The type strain is NIPH 2171(T) ( = CIP 110486(T) = CCUG 26390(T) = CCM 8555(T)).
Keywords: fylogeneze; techniky typizace bakterií; RNA, Ribosomal, 16S; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; molekulární sekvence - údaje; hybridizace nukleových kyselin; Acinetobacter; DNA, Bacterial; DNA bakterií; Animals; lidé; Genes, Bacterial; Humans; zvířata; spektrometrie hmotnostní - ionizace laserem za účasti matrice; RNA ribozomální 16S; Bacterial Typing Techniques; Molecular Sequence Data; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Nucleic Acid Hybridization; bakteriální geny